In the name of honor : a novel - Patterson, Richard North (Henry Holt and Co., 2010)
Lt. Brian McCarran has returned traumatized from Iraq. He depends on his lifelong friendship with Kate Gallagher, who is married to his commanding officer, Capt. Joe D'Abruzzo. When Brian shoots and kills D'Abruzzo, Capt. Paul Terry must defend him in a high profile court martial.